Origin of Heart Rate Variability and Turbulence: An Appraisal of Autonomic Modulation of Cardiovascular Function - Lombardi, Federico (Frontiers in Physiology, 2011)
Assessment of autonomic modulation of sinus node by non-invasive techniques has provided relevant clinical information in patients with several cardiac and non-cardiac diseases and has facilitated the appraisal of neural regulatory mechanisms in normal and diseased subjects. The finding that even during resting conditions the heart period changes on a beat to beat basis and that after a premature ventricular beat there are small variations in RR interval whose measurements may be utilised to evaluate the autonomic modulation of sinus node, has provided unprecedented clinical and pathophysiological information. Heart rate variability (HRV) and Heart Rate Turbulence (HRT) have been extensively utilised in the clinical setting. To explain the negative predictive value of a reduced HRV it was determined that overall HRV was largely dependent on vagal mechanisms and that a reduction in HRV could reflect an increased sympathetic and a reduced vagal modulation of sinus node; i.e. an autonomic alteration favouring cardiac electrical instability. This initial interpretation was challenged by several findings indicating a greater complexity of the relationship between neural input and sinus node responsiveness as well as the possible interference with non-neural mechanisms. Under controlled conditions, however, the computation of low and high frequency components and of their ratio seems capable of providing adequate information on sympatho-vagal balance in normal subjects as well as in most patients with a preserved left ventricular function, thus providing a unique tool to investigate neural control mechanisms. Analysis on non-linear dynamics of HRV has also been utilised to describe the fractal like characteristic of the variability signal and proven effective to identify patients at risk for sudden cardiac death. A reduction on HRT parameters reflecting reduced baroreflex sensitivity as a likely result of a reduced vagal and of an increased sympathetic modulation of sinus